Systemic immune-inflammation index predicted presence and severity of coronary artery disease (Annals of Medical Research, 2022)
Aim: We investigate whether the systemic immune-inflammation index (SII), an easily evaluated inflammatory and immune response marker, is associated with the SYNTAX score (SS) in patients admitted with suspected CAD who underwent coronary angiography (CAG).Materials and Methods: Evaluated retrospectively were 456 patients who underwent CAG in the cardiology outpatient clinic between January 2020 and January 2022. The SII was calculated by the following formula: neutrophils × platelets / lymphocytes. SS values were divided into 3 groups; low group (